Sounding the Alarm! Between Habituation and Mobilization - Drozdowski, Rafał; Szlendak, Tomasz (Studia Socjologiczne, 2026)
The dominant narrative regarding state and society in sociology today emphasizes ways of coping with contemporary threats and risks that seek to domesticate and normalize them, or that negate them. This narrative results in the overshadowing of anti-habituation strategies, understood as various methods of social mobilization. This article attempts to answer three questions: First, what are the manifestations of habituation, which are oriented towards by state institutions, individuals, and entire communities? Second, what are the most important determinants of this phenomenon? And third, can we speak of its reverse, as various anti-habituation strategies?